Rheumatic conditions associated with interstitial lung diseases: real-world outcomes in a secondary care setting - Alex Francioni; Muhammad K Nisar; Natasha Ramsundar; Vijay Joshi; Judeson Gnanapragasam (Monaldi Archives for Chest Disease)
Management of rheumatic conditions associated with interstitial lung disease (r-ILD) requires expertise, often occurring in tertiary referral centers. We set up a combined rheumatology and respiratory service in a district general hospital (DGH) to avoid long patient journeys and improve experience. We evaluated the outcomes of 104 patients managed in this pilot service model. Referrals were triaged in monthly ILD multidisciplinary team meetings, and appropriate patients were booked into the clinic. All data were recorded electronically with full access to demographics, disease parameters, investigations, and drug management. Of the patients who attended follow-up, 51 (51%) had stable or improved symptoms, 58 (67%) had stable or improved computed tomography imaging, 50 (78%) had stable or improved forced vital capacity, and 40 (77%) had stable or improved diffusing capacity of the lungs for carbon monoxide. There were similar improvements in 6-minute walk tests. A total of 27 patients died, with 33% of these deemed as a direct result of their ILD. Our report confirms that r-ILD can be successfully managed in a DGH setting, with a large cohort obtaining good comparable clinical outcomes. We show that r-ILD services can be established locally to help overstretched tertiary care while developing local expertise in the management of r-ILD.